1997
DOI: 10.3928/0191-3913-19970701-11
|View full text |Cite
|
Sign up to set email alerts
|

Transscleral Diode Laser Cyclophotocoagulation for Refractory Pediatric Glaucomas

Abstract: Purpose: To evaluate the success of contact transscleral cyclophotocoagulation (TDC) in patients with refractory pediatric glaucomas. Methods: Twenty-six eyes of 20 patients with therapyresistant pediatric glaucomas were included in this retrospective study. Subgroup analysis was performed for patients 10 or younger and patients older than 10 at time of first TDC procedure. Diode laser cyclophotocoagulation was applied using a fiber optic G-probe. Follow up until time of failure or for a minimum of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 7 publications
0
33
0
Order By: Relevance
“…Notably, the retinal detachment complications present in both studies were isolated to aphakic patients. Finally, Bock et al18 reported one patient out of 26 eyes developed a total retinal detachment following 113.4 J of total energy (2100 mW × 2000 ms × 27 shots × 360 deg, mean age 12.1 y). These results may indicate a dose-response relationship between delivered cyclodiode energy and complication rates, and utilizing a lower power or number of treatment spots may avoid the retinal complications reported in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the retinal detachment complications present in both studies were isolated to aphakic patients. Finally, Bock et al18 reported one patient out of 26 eyes developed a total retinal detachment following 113.4 J of total energy (2100 mW × 2000 ms × 27 shots × 360 deg, mean age 12.1 y). These results may indicate a dose-response relationship between delivered cyclodiode energy and complication rates, and utilizing a lower power or number of treatment spots may avoid the retinal complications reported in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…These results may indicate a dose-response relationship between delivered cyclodiode energy and complication rates, and utilizing a lower power or number of treatment spots may avoid the retinal complications reported in our patient. All 3 studies [16][17][18] similarly found the retinal detachment complications to occur in the months following cyclodiode treatment and, apart from 2 eyes that underwent YAG cycloablation prior, were presumed to be unrelated to previous procedures. In addition, PVR complications have not been reported following glaucoma filtration surgery and are unlikely to be the cause of PVR development in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with continuous wave TSCPC (CW-TSCPC) include conjunctival burns, hypotony, phyhisis, uveitis, cataracts, retinal detachment, scleromalacia, and vision loss. These are reported to be up to 18%, and more common in eyes with successive treatments or in eyes with already low vision (61,(63)(64)(65)(66).…”
Section: Cyclodestructionmentioning
confidence: 99%
“…With transscleral application, the success rate ranges from 30% to 79% with retreatment in about 70% of patients. [54][55][56][57] Using endoscopic application, the success rate has been reported 64% at 1 year and 16% by 5 years. Endoscopic retreatment brings the success rate up to 81% at 1 year and 34% at 5 years.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Success has been unpredictable. With transscleral application, the success rate ranges from 30% to 79% with retreatment in about 70% of patients 54–57. Using endoscopic application, the success rate has been reported 64% at 1 year and 16% by 5 years.…”
Section: Introductionmentioning
confidence: 99%